PENGGUNAAN METODE LATIHAN 3-POINT 5-POST DRILL TERHADAP EFEKTIVITAS AKURASI SHOOTING 3 POINT TIM PUTRA BOLABASKET PORPROV KABUPATEN LUMAJANG - EKA CAHYONO, DARY; WISMANADI, HIMAWAN (Jurnal Kesehatan Olahraga, 2019)
ABSTRACTBasketball is one of the favorite sports or popular with the people now and is a sport that is rapidly developing.technique Shooting is one technique that must be mastered by basketball players. 3 point 5 post drills is one of the training methods that can increase the accuracy of 3 point shoots. The purpose of this study was to find out the use of thetraining method 3 point 5 post drill on the effectiveness ofaccuracy for 3 point shooting the mens projection team at the Porprov Projection in Lumajang Regency. This research method uses descriptive quantitative design withresearch pretest and posttest. The sample of this study was 10 athletes from basketball men. The results of this study obtained an average pretest of 5.30 and at the posttest of 10.30. Based on the normality test thedata pretest and posttest obtained significant results, namely sig. 0.200> 0.05 and the data is declared to be normally distributed. Calculation of the average difference test before and after based on statistical calculations using theformula paired smp t-test obtained a significant level of 0.00, it can be stated that there is a difference between the results of the pretest and posttest. So it can be concluded that there is a significant influence on the use of thetraining method 3 point 5 post drill on the effectiveness of theaccuracy of 3 point shooting the mens projection team at Porprov Lumajang Regency.Key Word: Bolabasket, 3 point 5 point drill, 3 point shooting